The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1212/01.wnl.0000113727.73153.68
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Parkinson disease and parkinsonism in three elderly populations of central Spain

Abstract: Incidence estimates of PD based on two-phase investigation methodology are higher than those based on other approaches. Men had a risk of developing PD that was twice that of women. A large proportion of PD patients may never seek neurologic attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
143
1
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(171 citation statements)
references
References 40 publications
15
143
1
11
Order By: Relevance
“…Some studies, including our investigation, found a decline in incidence rates for the oldest old,14, 15, 16, 17, 18 and others did not 11, 12, 13. However, varying definitions and small sample sizes make comparisons difficult 1.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Some studies, including our investigation, found a decline in incidence rates for the oldest old,14, 15, 16, 17, 18 and others did not 11, 12, 13. However, varying definitions and small sample sizes make comparisons difficult 1.…”
Section: Discussionmentioning
confidence: 51%
“…Incidence rates are also low for those aged 50‐59 and increase sharply afterward. Age‐specific peaks differ between studies, however, ranging from 80.4 to 678 new cases/100 000 person‐years 11, 12, 13, 14, 15, 16, 17, 18, 19. German data on prevalence and incidence are rare, outdated, and had been designed primarily as door‐to‐door surveys 1.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed of the study population and sampling methods have been published elsewhere. [4][5][6] Briefly, subjects were selected by means of census lists from three different populations in central Spain in 1994-1995. Data from this baseline cross-sectional evaluation were used for this study.…”
Section: Study Populationmentioning
confidence: 99%
“…5,6 PD was defined by the presence of 2 cardinal signs of bradykinesia, resting tremor, rigidity and impairment of postural reflexes (or 1 cardinal sign in those on antiparkinsonian medication) and exclusion of other causes of parkinsonism. Only subjects with idiopathic PD were included in the study (Table 1).…”
Section: Diagnosis Of Parkinson's Disease and Diabetesmentioning
confidence: 99%
“…Data for these analyses were derived from the Neurological Disorders in Central Spain (NEDICES) study, a longitudinal, population-based survey of the prevalence, incidence, and determinants of major ageassociated conditions of the elderly, including Parkinson's disease, essential tremor, stroke, and dementia [16][17][18][19][20][21][22][23][24][25]. Detailed accounts of the study population and sampling methods have been published [23][24][25].…”
Section: Study Populationmentioning
confidence: 99%